One pup's up - Chall, Marsha Wilson; Cole, Henry 1955- (New York Margaret K. McElderry Books, 2010)
Rhyming text counts off ten puppies as they awaken one by one, chase and bounce around the house, eat kibble and get washed, then fall back to sleep.
Ages 1-4.
Keywords: Stories in rhyme; Dogs -- Fiction; Animals -- Infancy -- Fiction; Counting